2017
DOI: 10.24815/siele.v4i1.7004
|View full text |Cite
|
Sign up to set email alerts
|

Using Think-Pair-Share for writing descriptive texts

Abstract: Using the right technique to teach writing is very important to help students

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Students also highlighted on experiencing a heightened level of writing skills after receiving cooperative learning training, which is in line with the works of Sahardin, Hanum & Gani (2017) and Yusuf et.al. (2019).…”
Section: Discussionsupporting
confidence: 85%
“…Students also highlighted on experiencing a heightened level of writing skills after receiving cooperative learning training, which is in line with the works of Sahardin, Hanum & Gani (2017) and Yusuf et.al. (2019).…”
Section: Discussionsupporting
confidence: 85%
“…The studies showed that TPS gave positive effect on improving students writing skill. Sahardin stated that the results showed TPS technique was effective for improving the students' mastery of organization, vocabulary and content in descriptive text [5]. From that research found the students got more progress in writing skill especially the mastery of organization and the improvement in vocabulary [5].…”
Section: Introductionmentioning
confidence: 94%
“…Sahardin stated that the results showed TPS technique was effective for improving the students' mastery of organization, vocabulary and content in descriptive text [5]. From that research found the students got more progress in writing skill especially the mastery of organization and the improvement in vocabulary [5]. Sumarsih and Sanjaya also found that the students' achievement in writing is improved when they are taught by using TPS Technique [6].…”
Section: Introductionmentioning
confidence: 95%
“…Some studies suggest that involving students in such process-oriented writing activities can help them cope with the aforementioned issues (Sutrisno et al, 2018;Yusuf et al, 2019). Sahardin et al (2017) conducted a pre-experimental study (n=14) examining the effect of using a Think Pair Share technique on students' writing skills. The study revealed that this cooperative technique could significantly improve students' writing scores in terms of organization, vocabulary, and content.…”
Section: Introductionmentioning
confidence: 99%